TACTICS AND TREATMENT OF BLEEDING OF DILATED VARICOSE VEINS OF THE ESOPHAGUS AND STOMACH IN CHILDREN WITH PORTAL HYPERTENSION - Abduvalieva Chulpanoy Muhammadzhonovna (Galaxy International Interdisciplinary Research Journal, 2024)
The effectiveness of providing qualified medical care for portal hypertension syndrome and esophagogastric bleeding in children depends on timely diagnosis, timely stopping of bleeding, if necessary, and adequate surgical treatment. However, when hospitalized later than 1-2 days from the onset of the first signs of bleeding, the outcome is largely determined by the methods used to stop bleeding, their pathogenetic correspondence to the patterns of development of liver and multiple organ failure. Treatment of portal hypertension syndrome and bleeding from varicose veins of the esophagus and stomach includes a therapeutic and prophylactic complex of measures: drug therapy, placement of a Blackmore probe, endoscopic ligation and sclerotherapy, and, if absolutely necessary, surgical treatment. Timely diagnosis makes it possible to identify the disease in the compensated and subcompensated stages, which greatly facilitates treatment and reduces mortality.